Multimodal Coherence Revisited: Notes on the Move From Theory to Data in Annotating Print Advertisements - Stöckl, Hartmut; Pflaeging, Jana (Frontiers in Communication, 2022)
The present paper proposes a preliminary annotation framework for the study of multimodal coherence in print ads. The framework is firmly based on a review of current theorizing on multimodal cohesion and coherence. Following guidelines for good empirical practice, the annotation scheme is tested on 50 ad samples, seeking to illustrate genre-specific qualities of multimodal coherence and to identify difficulties in applying conceptual frameworks to data. The paper employs six dimensions of multimodal coherence: layout, cohesive ties, info-linking, relational propositions, mode-centricity and multimodal rhetorical operations. In conclusion, we outline some of the more general challenges that multimodal annotation raises when it makes close contact with data.